Patelofemoralni bolečinski sindrom - Tonin, Katarina (Rehabilitacija (Ljubljana), 2012)
Patellofemoral pain syndrome (PFPS) is a common reason for absence from training in sports involving repetitive jumping, squatting, direction-changes or long-distance running. The main cause for PFPS is altered biomechanics of the lower limb. Therefore, the equilibrium of patellofemoral force-couples is the main focus of PFPS rehabilitation and prevention programs. The purpose of this article is to characterize PFPS and its risk factors, to present main PFPS-related biomechanical discrepancies of the lower limbs, and to describe diagnostic procedures and individually adjusted rehabilitation protocol.
Keywords: Biomechanics; biomehanika; dejavniki tveganja; Diagnostic Techniques and Procedures; diagnostika; individually adjusted rehabilitation; Lower Extremity; Patellofemoral Pain Syndrome; patelofemoralni bolečinski sindrom; rehabilitacija; Risk Factors; spodnje ekstremitete; spodnji udi; vocational rehabilitation